Analysis of Business Actors' Perceptions and Business Sizes on The Implementation of Sak Emkm in The Fashion Sector in Padang City - Frity Ayu Azhari; Elsa Meirina; Dewi Zulvia; Desyani Umar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2026)
This study aims to analyze the influence of business owners' perceptions and company size on the implementation of Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM) in the fashion sector in Padang City. This study uses a quantitative method with a multiple linear regression approach. The population consisted of 340 MSMEs, with a sample of 80 respondents selected using a convenience sampling technique. The data used are primary data collected through questionnaires. The results show that business owners' perceptions have a positive but insignificant influence on the implementation of SAK EMKM. This indicates that although these perceptions are beneficial, they have not fully encouraged business owners to implement accounting standards, because these standards are still considered complex. Meanwhile, company size has a positive and significant influence on the implementation of SAK EMKM, meaning that the larger the business, the greater the need and ability to prepare financial reports in accordance with these standards. At the same time, business owners' perceptions and company size have a significant influence on the implementation of SAK EMKM.